Investigating the relationship between: urban identity, quality of urban life, and urban physical form in Iranian new towns - Derakhshan, Mahsa (Technische Universität Dortmund, 2021)
New Towns in Iran have been located, planned, and built near the big cities since early 1981 to attract the overflow population of metropolises and reduce the density of the mother cities. Andisheh is one of the Iranian new towns that was built in 1992 in a 30 kilometers distance from the metropolis of Tehran. Despite the efforts of the planners and urban designers in locating new towns, and designing open spaces, squares, streets, parks, appropriate width of roadways, and residential complexes, new towns lack something. Their urban spaces are not attractive for their inhabitants, residents are not satisfied with the quality of the urban environment and they tend to leave new towns. Moreover, most of the new towns are faced with such problems as being a dormitory for their residents. It is important to study the quality of urban life and urban identity related to physical form in urban areas such as new towns since urban physical form affects perceptual aspects of residents, so perceived quality of life, sense of belonging, and sense of place. Human perception and experience of their surrounding urban spaces and QOUL affect the behavior of residents. Urban identity is related to the identity of residents and also the identity of the city. The urban environment reflects its resident’s needs and values and all of the residents are part of their cities, because, without citizens, the cities would not be what they are. The present research investigates the relationship between the quality of urban life (QOUL), urban identity (UI), and urban physical form (UPF) in Andisheh new town focusing on density, housing, land use, layout, and accessibility. This study includes descriptive, analytical, and explorative research, in which a mixed-method approach including the qualitative and quantitative methods – a case study approach and a quantitative descriptive method- is utilized. The methods used in this research are (1) the literature review and theoretical analysis, (2) questionnaire to survey the case study with a sample of 413 questionnaires filled by residents, (3) the qualitative method to obtain fundamental knowledge and to collect information through the interview with urban experts, (4) quantitative method, to collect numeric and statistical data and finally, (5) Space Syntax analysis, GIS, and statistical methods including SPSS using KMO and Bartlett’s Test of Sphericity and CFA, and SEM (structural equation modeling) through AMOS. The Space Syntax Theory is employed by measuring the value of connectivity, integration, and mean depth. GIS has been used to evaluate the spatial scattering of land uses, and geocode the locations of the residents (through their addresses), and creating a set of geodatabase containing all the questions of questionnaires. Data collected through questionnaires and geocoded in GIS has been analyzed through SPSS and AMOS. The SEM is applied to analyze the relationship between indicators of QOUL, UI, and UPF, as well as, the correlation between these dimensions. The hypotheses of this study, which are the main hypotheses of the research (HI and HII) and subsidiary hypotheses (H1- H9) related to each dimension, are analyzed through SEM analysis. The value of the path coefficient represents that if there is a positive, negative, or no significant correlation between variables. Therefore, the results of SEM analyses indicate two types of acceptable or not significant correlation. The acceptable positive correlations are between: dimensions of UI and QOUL with the value of 0.87 (HI), objective measures of housing and satisfaction with housing with the value 0.32 (H2), activities and meaning with the value 0.12 (H4), objective measures of housing and objective measures access with the value 0.48 (H7), objective measures of housing and objective measures of land use with the value 0.52 (H7), objective measures of housing and objective measures of density with the value 0.42 (H7), objective measures of access and objective measures of land use with the value 0.39 (H7), subjective measures of access and overcrowding with the value 0.57 (H8), subjective measures of layout and overcrowding with the value 0.61 (H8), and subjective measures of access and subjective measures of layout with the value 0.77 (H8). The negative acceptable correlations are between: UF and QOUL with the value -0.64 (HII), UF and UI with the value -1.30 (HII), objective density and satisfaction with overcrowding with the value -0.53 (H1), mean depth and satisfaction with land uses -0.22 (H6), and between objective measures of land use and objective measures of density with the value - 0.61 (H7). The results represent that there is not a significant correlation between: objective density and perceived overcrowding (H1), objective measures of land use and satisfaction with land use (H3), physical setting and meaning (H4), physical setting and activities (H4), objective measures of accessibility and subjective measures of accessibility (H5), objective measures of access and objective measures of density (H7). It is significant to note that the results and findings are based on the questionnaires that were filled out by the residents of Andisheh new. Therefore, the correlations between variables may have a different outcome in other cities. As a summary of the conclusion of the present research in Andisheh new town, it can be pointed out that although there may not be a significant relationship between some indicators of UI, QOUL, and UPF, but in general, there is a strong relationship between UI and QOUL in Andisheh new town. Moreover, UPF affects UI and QOUL, and this relationship is strong and negative. Keywords: quality of urban life (QOUL), urban identity (UI), urban physical form (UPF), geocoding the location of residents, analysis of population and density/ housing/ accessibility/ urban layout/ and land use, Space Syntax analysis, structural equation modeling (SEM), the relationship between indicators of UI, QOUL, and UPF
Case study: Andisheh new town
Keywords: Quality of urban life; Urban identity; Urban physical form; Geocoding; Population & density; Housing; Access; Urban layout; Land use; Space Syntax; SEM; 710; Iran; Trabantenstadt; Stadtplanung